Pengaruh Pengetahuan Pengelola Berkah Mart di Kabupaten Bangka Selatan Terhadap Implementasi SAK EMKM dalam Penyajian Laporan Keuangan - Fadila Nabila; Rahmat Ilyas; Marheni Marheni (JYRS: Jurnal Online Mahasiswa Program Studi Fakultas Syariah dan Ekonomi Islam, 2022)
The results of this study indicate that the level of knowledge of Berkah Mart managers in South Bangka Regency about SAK EMKM is still low. This is evidenced respectively by 78.9% and 71.1% of respondents stated that the financial statements prepared based on SAK EMKM are difficult to understand and they still make financial reports in the form of reports of cash receipts and disbursements only so that they are not in accordance with SAK EMKM . This study also shows the results that the knowledge variable has a positive effect on the implementation of SAK EMKM in the presentation of financial statements, this can be seen from the results of the t-test with a value of tcount (5.351) > ttable (2.02809) with a significant level of tcount (0.000) < ttable (0.05). The results of the coefficient of determination test (R2) that the independent variable (knowledge) of Berkah Mart managers in South Bangka Regency is 44.3% influenced by the dependent variable (implementation of SAK EMKM) in the presentation of financial reports. While the 55.7% side is influenced by other variables not examined in this study.